KAJIAN REVITALISASI PASAR PLERET KABUPATEN BANTUL - Prihatno, Prihatno (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2016)
The existence of traditional markets that have unique functions and diversity must be preserved and conserved as one characteristic of the culture in the district of Bantul in particular because there are values that are not contained in a modern shopping center. This has encouraged the government is obliged to immediately revitalize traditional markets in order to respond to the chronic problems of the traditional market which is related to the traditional market image problem. Traditional markets imaged as a rundown, dirty, muddy, poorly maintained, and has a quality level of occupancy very rendah.Program traditional market revitalization aims to improve the performance and quality of the market Review activity Market Revitalization Pleret intended to identify the physical, economic, management, environmental and social, in order to obtain data that can be used to find out the problems and constraints faced by market Pleret development efforts as a traditional market better, formulate. Market revitalization programs and activities Pleret Bantul and provide recommendations on structuring the physical aspects, economics, management, socio-cultural environment and Pleret Pasar Bantul. The results showed that Pleret Market is a traditional market with pancawara or use the 'market'. namely a market which used 'pasara' which consisted of five days a week, namely PON‟, Legi, Pahing, Pon and Wage. And the market Pleret uses only two days is the day with the 'market' Pon and day with the 'market' PON‟ while other days by Legi, Pahing and Wage in the market Pleret not move alias lid so that the count of time efficiency, the market Pleret including market inefficient because only open 12 days a month. In an effort to improve the image and power saing Pasar Pleret, it is recommended that the market Pleret can soon turn into a normal market, business should immediately take the policy with regard to improving the management of Market Pleret, so that this market can operate optimally and efficiently, serve the needs of society, merchants increase revenue, and increase revenue (PAD) through retribution market which will eventually boost economic growth Bantul. Keywords: Tradisional Markets and Revitalization